PEMANFAATAN LIMBAH KOLAM IKAN SEBAGAI SUMBER HARA N BAGI PERTUMBUHAN DAN HASIL JAGUNG MANIS (Jea mays saccharata ) DI LAHAN GAMBUT - Suparto H (Fakultas Pertanian Universitas Palangka Raya, 2016)
This study aims to assess the use fish pond wastes, such as pond’s water as source of N (nitrogen) for the growth and production of sweet corn that is grown on peatland. To test this experiment, statistically it was employ complete randomized design (CRD) with only one factor variable, fish pond water was divided into five different levels time to pour water : AL0 = control, AL1 = every 2 day, AL2 = every 4 day, AL3 = every 6 day dan AL4 = every 8 day and wich each three replication. Result showed that of fish pond’s water evry 4 day can increasing growth and production of sweet corn wich was planted on peatland farming area. The use of pond’s water as a source of N to sweet corn plantation of the peatland farming